2021
DOI: 10.1038/s41431-021-00879-w
|View full text |Cite
|
Sign up to set email alerts
|

What people really change after genetic testing (GT) performed in private labs: results from an Italian study

Abstract: Despite the widespread diffusion of direct-to-consumer genetic testing (GT), it is still unclear whether people who learn about their genetic susceptibility to a clinical condition change their behaviors, and the psychological factors involved. The aim of the present study is to investigate long-term changes in health-related choices, individual tendencies and risk attitudes in an Italian sample of GT users. In the context of the Mind the Risk study, which investigated a sample of Italian adults who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 46 publications
3
14
0
2
Order By: Relevance
“…In the present study, and in line with previous studies (McGrath et al, 2019 ; Oliveri et al, 2021 ; Oliveri, Marton, et al, 2020 ; Roberts et al, 2017 ), the sample of Italian GT users was predominantly female, young adult, married, well‐educated and without children. German GT users were divided fairly between men and women, with and without children, generally well‐educated and predominantly married or in a stable relationship.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In the present study, and in line with previous studies (McGrath et al, 2019 ; Oliveri et al, 2021 ; Oliveri, Marton, et al, 2020 ; Roberts et al, 2017 ), the sample of Italian GT users was predominantly female, young adult, married, well‐educated and without children. German GT users were divided fairly between men and women, with and without children, generally well‐educated and predominantly married or in a stable relationship.…”
Section: Discussionsupporting
confidence: 90%
“…A recent systematic review and meta‐analysis of 19 studies, conducted mainly in the United States, showed that GT users are more likely to improve their lifestyle, follow a healthier diet, increase exercise and medical preventive checks, and quit smoking (Stewart et al, 2018 ). Similar results were found in a very recent Italian study (Oliveri et al, 2021 ), where GT users reported high motivation to change health‐related habits reducing risky conditions, following a healthier diet, practicing more exercise, and improving medical preventive checks specifically (Oliveri et al, 2021 ; Oliveri, Marton, et al, 2020 ).…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations